PREFERENCE OF RESIDENTIAL TYPOLOGIES OF URBAN MALAYSIANS - Poh Im, Lim; Yun Fah, Chang (PLANNING MALAYSIA, 2018)
This paper seeks to understand patterns of residential preferences of urban Malaysians when seeking to purchase residential properties. Data was gathered through sampling surveys targeting potential house buyers in property fairs in three urban centres in Malaysia, namely Kuala Lumpur, Georgetown and Johor Bahru. Results highlighted significant presence of young purchasers and firsttime buyers; majority seeking to purchase properties priced RM600,000 and below; and taking very long tenure to finance the properties. Double-storey terrace and condominium, accumulatively garnered higher popular choice, but both fell short of ‘Most Preferred’ category. Factor analysis discovered that overall landed properties fared better than multi-storey buildings as preferred residential typology across the board regardless of socio-economic backgrounds. Family situation and circumstance, referring to marital status, number of family member, and whether they previously owned a property, were found to be the most crucial factors governing their choice on the preferred type of residential properties.